Ionic Liquids as Environmentally Benign Electrolytes for High‐Performance Supercapacitors. Issue 1 (23rd October 2018) - Shahzad, Suniya; Shah, Afzal; Kowsari, Elaheh; Iftikhar, Faiza Jan; Nawab, Anum; Piro, Benoit; Akhter, Mohammad Salim; Rana, Usman Ali; Zou, Yongjin
Abstract: Electrochemical capacitors (ECs) are a vital class of electrical energy storage (EES) devices that display the capacity of rapid charging and provide high power density. In the current era, interest in using ionic liquids (ILs) in high‐performance EES devices has grown exponentially, as this novel versatile electrolyte media is associated with high thermal stability, excellent ionic conductivity, and the capability to withstand high voltages without undergoing decomposition. ILs are therefore potentially useful materials for improving the energy/power performances of ECs without compromising on safety, cyclic stability, and power density. The current review article underscores the importance of ILs as sustainable and high‐performance electrolytes for electrochemical capacitors. Abstract : Supercapacitors hold great promise as proficient energy storage devices. However, these cannot store as much energy as conventional batteries. In this regard, replacement of conventional solvents with environmentally benign ionic liquids is a good approach to improve the energy performance of supercapacitors. Hence, this article underscores the importance of ionic liquids as sustainable and high‐performance electrolytes for supercapacitors.